Talking yourself out of exhaustion: the effects of self-talk on endurance performance - Blanchfield, A. W.; Hardy, J.; de Morree, H. M.; Staiano, W.; Marcora, S. M. (Medicine & Science in Sports & Exercise, 2014)
Purpose: The psychobiological model of endurance performance proposes that the perception of effort is the ultimate determinant of endurance performance. Therefore, any physiological or psychological factor affecting the perception of effort will affect endurance performance. Accordingly, this novel study investigated the effects of a frequently used psychological strategy, motivational self-talk (ST), on RPE and endurance performance.